2021
DOI: 10.1097/md.0000000000027283
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous golimumab induced and maintained clinical response in a child with a biological-experienced steroid-refractory flare of ulcerative colitis

Abstract: Introduction: Golimumab is a fully human antitumor necrosis monoclonal antibody that can be administered by either subcutaneous injection or intravenous infusion. Golimumab is approved for the treatment of the adults with rheumatic diseases, and ulcerative colitis, Whereas in children, golimumab is indicated only for the treatment of active polyarticular juvenile idiopathic arthritis. We have written on the off-label use of subcutaneous golimumab, which helped to induce and maintain remission on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[6] The only evidence for golimumab in pediatric UC was an open-label pharmacokinetic study and 2 case reports, resulting in a weak recommendation. [19][20][21][22] Except in a few instances, Ustekinumab was administered after other biologics had failed. [23][24][25] Infliximab was the most commonly reported failed biologic, as expected, and Table 2 summarizes reports on Ustekinumab in pediatric IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6] The only evidence for golimumab in pediatric UC was an open-label pharmacokinetic study and 2 case reports, resulting in a weak recommendation. [19][20][21][22] Except in a few instances, Ustekinumab was administered after other biologics had failed. [23][24][25] Infliximab was the most commonly reported failed biologic, as expected, and Table 2 summarizes reports on Ustekinumab in pediatric IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoassays for measuring serum levels of golimumab and golimumab antibodies were comparable in quality, but the quantitative results were not, emphasizing the importance of using the same assay to consistently monitor a patient's treatment [ 16 ]. We previously used golimumab with 200/100 then 50 mg every four weeks to treat acute severe ulcerative colitis low-weight child, which helped him to achieve clinical and endoscopic remission [ 17 ]. This case demonstrated that golimumab with 200 mg, 100 mg at week 0, 2 then 50 mg every four weeks may be safe and effective in the treatment of pediatric chronic active ulcerative colitis in low weight children.…”
Section: Discussionmentioning
confidence: 99%